Faktor Penyebab dan Upaya Penanggulangan Disparitas Putusan Bagi Pelaku Tindak Pidana Kekerasan Seksual di Wilayah Hukum Pengadilan Negeri Kelas I A Kupang - Maryo Jaxel Mabilehi; Rudepel Petrus Leo; Heryanto Amalo (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The judge's decision is a vital aspect needed to resolve criminal cases. The judge's authority and power are so great in deciding cases that result in disparities in verdicts in cases where the weight of the crime is the same, namely cases of sexual violence against children. This research is an empirical juridical research, so the data sources used are primary data sources, secondary data sources and tertiary data sources. Primary data sources are obtained through the results of research in the field, secondary data is obtained through literature, laws, and other literature, and tertiary data is obtained through dictionaries, mass media, and the internet. The data were analyzed in a descriptive-qualitative manner. The results of the study show that: (1) the factors that cause the disparity in punishment for perpetrators of sexual violence are internal factors and external factors of judges. (2) efforts to overcome disparities in the verdicts of sexual violence crimes which include repressive efforts and preventive efforts.